A Study on Water-Induced Damage Severity on Diesel Engine Injection System Using Emulsified Diesel Fuels - Min-Seop Kim (Electronics, 2021)
Diesel engine emissions contribute nearly 30% of greenhouse effects and diverse health and environmental problems. Amidst these problems, it is estimated that there will be a 75% increase in energy demand for transportation by 2040, of which diesel fuel constitutes a major source of energy for transportation. Being a major source of air pollution, efforts are currently being made to curb the pollution spread. The use of water-in-diesel (W/D)-emulsified fuels comes as a readily available (and cost-effective) option with other benefits including engine thermal efficiency, reduced costs, and NOx reduction; nonetheless, the inherent effects—power loss, component wear, corrosion, etc. still pose strong concerns. This study investigates the behavior and damage severity of a common rail (CR) diesel fuel injection system using exploratory and statistical methods under different W/D emulsion conditions and engine speeds. Results reveal that the effect of W/D emulsion fuels on engine operating conditions are reflected in the CR, which provides a reliable avenue for condition monitoring. Also, the effect of W/D emulsion on injection system components-piston, nozzle needle, and ball seat–are presented alongside related discussions.